SISTEM INFORMASI PENERIMAAN KARYAWAN BARU PADA PT. BATANG NARAS JAYA BERBASIS WEB - Ronaldo Ronaldo; Susy Rosyida (Jurnal ilmiah Sistem Informasi dan Ilmu Komputer, 2022)
Web-Based New Employee Acceptance Information System. A company in recruiting employees must follow developments. PT. Batang Naras Jaya in handling the acceptance of new employees still uses a manual system which is considered not effective and efficient enough in dealing with the problem of hiring new employees because it takes longer time to process the application form, it is still manual with paper, the applicant's personal data is also filled in by hand. paper, reading files and several tests carried out by the HRD section must be carried out one by one if there are many applicants in one day, of course, this will result in a queue for the test. With a computerized website-based system to help companies improve time efficiency in accepting new employees to be more effective, efficient, safe, fast and accurate. The method used in developing this software uses the Rapid Application Development (RAD) method. The web design application used is Visual Studio Code (vsc) and for the programming language it uses PHP and uses the MySQL database. With the existence of a new employee recruitment information system at the company, it is hoped that it can help facilitate the process of data collection, selection and the process of accepting new employees at the company. which can help increase work productivity and can present employee data at the company, especially in terms of accepting new employees at the company. the selection of new employees is more controlled with the new employee acceptance information system and makes it easier to make new employee acceptance reports at the company.